KOMUNIKASI CYBER CORPORATE SOCIAL RESPONSIBILITY (CSR) (ANALISIS PEDOMAN PELAPORAN GRI PADA OFFICIAL WEBSITE PT. MAYORA INDAH, TBK) - Maylanny Christin (JCommsci - Journal Of Media and Communication Science, 2020)
This study is entitled "Cyber Corporate Social Responsibility Communication (Analysis of Global Reporting Initiative Reporting Guidelines on the Official Website of PT. Mayora Indah, Tbk). This study aims to determine the form of message content and the appropriateness of the Global Reporting Initiative reporting. The importance of Corporate Social Responsibility communication that is managed extensively to create a reputation and maintain long-term corporate sustainability. The development of cyber information technology makes it easier for stakeholders to gain access to Corporate Social Responsibility communication, one of which is by utilizing official websites as accurate Corporate Social Responsibility information. During a pandemic like this, websites are considered increasingly important for a company. Having a website means the company is starting to position itself to be more advanced and professional to give an impression to the stakeholders. In the midst of lifestyle #dirumahaja marketing through online sites and digital branding must be a choice for stakeholders. The excellence of the interactive website makes the platform utilized as a Corporate Social Responsibility communication medium that has been actualized by many companies in Indonesia, one of which is the company PT. Mayora Indah, Tbk.Keywords: Corporate Social Responsibility Communication; Global Reporting Initiative; Official Website.